Krinolin, korsett, kaftan – om kläder, genus och kulturanalys: En promotionsföreläsning och dess rituella sammanhang - Meurling, Birgitta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2019)
The main focus of this article is the doctoral conferment ceremony lecture, I gave as the promotor of the Faculty of Arts at Uppsala university the 1st of June 2018. In this article I describe the conferment ceremony and publish my lecture, which is shortly summarized below. They say that clothes make the man – a saying that requires qualification. However, it is obviously true that our clothing shapes us in many ways, and sends multiple signals. Clothes can e.g. show what group we belong to, our taste in music or our political preferences. The Beatles made long hair fashionable for men, punk made safety pins cheek piercings a fashion statement. Different professional groups dress in official and unofficial uniforms, for practical or ideological reasons. Our clothes declare who we are or want to be, whether we want to fit in or stick out. They are an ingenious symbolic system, a mirror of society that can reveal the structure of hierarchies, gender orders and religious systems.